Effectiveness of the Backhand Netting Technique in Badminton: A Performance Analysis - Diego Arya Jayawardhana; Fajar Awang Irawan (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
Backhand netting is an essential skill in badminton, helping players control the pace of play while creating scoring opportunities. Its effectiveness depends on shuttlecock placement accuracy, trajectory quality over the net, and its ability to land where the opponent struggles to reach it. This study aimed to describe the effectiveness of the backhand netting technique among athletes of the Badminton Student Activity Unit (UKM) at Universitas Negeri Semarang and identify its contributing biomechanical factors. A descriptive-correlational quantitative approach was used, involving ten male athletes selected through purposive sampling. Data were collected through a backhand netting skill test with three assessment indicators and 2D kinematic video analysis using Kinovea software, then analyzed using descriptive statistics and Pearson correlation. Results showed a mean effectiveness score of 10.10 out of 12, with eight athletes (80%) classified as very effective and two (20%) as effective. Kinematic analysis further revealed a significant, strong positive correlation between the final elbow angle during follow-through and effectiveness score (r = 0.692, p = 0.027). Overall, the athletes' backhand netting technique was highly effective, driven mainly by optimal elbow extension during follow-through, offering coaches valuable insight for evaluating technical performance through biomechanical technology.